Elastohydrodynamic lubrication and wear modelling of the knee joint replacements with surface topography. Issue 1 (22nd March 2018) - Gao, Leiming; Hua, Zikai; Hewson, Robert; Andersen, Michael Skipper; Jin, Zhongmin
Abstract : This numerical study predicted wear of lubricated total knee replacements with the existing of textured surface and the possibility of surface designs to reduce wear. In the first part, a wear model of metal‐on‐polyethylene total knee replacement was developed. The medial and lateral knee compartments was accounted for separately, with the contact force and motion during walking cycles applied. An adapted Archard wear formula was employed where the wear factor was an exponential function of the 'Lambda ratio' (film thickness to the average roughness). Wear of the soft bearing surface (polyethylene insert) was simulated with regularly geometry update until a steady‐state wear observed. In the second part, the effect of surface topography of the knee replacements was investigated. The surface texturing techniques have shown promising benefit to machine components in many areas of engineering practice. The texture parameters were designed using the Taguchi method for the geometry, size, and distribution of the micro dimples. It was observed that the lateral compartment may benefit from surface texturing if dimples were properly designed, while the texturing showed hardly advantageous effect on the medial surface in terms of lubrication enhancement and wear reduction. Some results were presented in the 6th World Tribology Conference.